Telegram - Schevenels, Walther, b. 1894
029-0033-001 F POST OFFICE OVERSEAS TELEGRAM Received at Central Telegraph Office From Telegrams for all countries in the world and radio-telegrams for ships on all seas are accepted at all Postal Telegraph Offices or may be telephoned to the Post Office. No. 0383 Office Stamp LONDON SWDO 21 JAN 38 21 JAN 1938 To Official particulars, including Office of Origin. + 152 PARIS 28527 21 21 1235- TEWSON TRADUNIC SOWEST LDN = ANY AMOUNT GOODS FOR SPAIN CAN BE CONSIGNED TO EDOUARD AGET 101 BOULEVARD STRASBOURG LE HAVRE = SCHEVENELS = CT 101 + For free repetition of doubtful words telephone NATIONAL 3383. If the telegram was received by telephone DIAL 559. This form and if possible the envelope should accompany any written enquiry. 292/946/29/33